Estimation of Periostin and Tumour Necrosis Factor-α in Type II Diabetics with Chronic Periodontitis: A case-control study - Burra Naga Radhika; Deva Priya Appukuttan; Ponnudurai Samuel Gnana Prakash; Sangeetha Subramanian; Dhayanand John Victor; Aruna Balasundaram (Wolters Kluwer Medknow Publications, 2019)
Background: Periostin, a matricellular protein, is downregulated in chronic inflammatory periodontal disease and is negatively modulated by tumor necrosis factor-α (TNF-α) in human periodontal fibroblast cell culture. The study aimed to estimate the gingival crevicular fluid (GCF) levels of periostin and TNF-α and to discern their relationship in chronic periodontitis (CP) individuals with and without Type II diabetes mellitus (DM). Materials and Methods: A total of 60 participants were divided into three groups, with 20 in each group. Group I - systemically and periodontally healthy, Group II - generalized CP, and Group III - generalized CP with Type II DM. Plaque index, gingival index, sulcular bleeding index, probing depth, and clinical attachment level were recorded. GCF periostin and TNF-α were quantified using the enzyme-linked immunosorbent assay. Results: Intergroup comparison was performed using the one-way ANOVA and Kruskal-Wallis. The relationship between the variables was analyzed using the Pearson's and Kendall's Tau correlation. The GCF periostin levels in Groups I, II, and III was 27.52 ± 2.39 ng/mL, 20.18 ± 1.42 ng/mL, and 16.77 ± 3.29 ng/mL, respectively. The GCF TNF-α levels in Groups I, II, and III was 92.41 ± 19.30 ng/L, 118.53 ± 21.93 ng/L, and 147.67 ± 16.35 ng/L, respectively. Periostin decreased, and TNF-α increased in periodontal disease; moreover, periostin level correlated negatively with all the site-specific clinical parameters whereas TNF-α positively correlated (P < 0.001). Conclusions: TNF-α strongly and negatively downregulates periostin in a chronically inflamed locale leading to compromised integrity of the periodontium.